Perceived discrimination and satisfaction with life among ethnic minorities in the COVID-19 pandemic context - Costa, Sarah Andrea Rosa (2022)
The present investigation examined the effects of the pandemic on perceived discrimination and satisfaction with life among people from ethnic minorities within the Portuguese population. Furthermore, we analyzed the moderating role of ethnic identity in the relationship between ethnic identification with an ethnic minority and perceived discrimination. Thus, it was predicted that higher levels of ethnic identity would diminish perceived discrimination. We also compared the study variables and the level of “concern regarding the COVID-19 pandemic” among the ethnic minority and majority groups. This transversal and correlational study, carried out through an online questionnaire, counted with a total of 231 respondents, 142 participants on ethnic majority group and 89 participants on the ethnic minority group. The measures Everyday Discrimination Scale (in the COVID-19 context), Satisfaction with Life Scale, and an adaptation version of the Multigroup Ethnic Identity Measure, were used in the questionnaire to analyze the study’s variables. Results showed that the relationship between ethnic identification, with an ethnic minority, and satisfaction with life is mediated by perceived discrimination. They also showed that people from the ethnic minority group with high ethnic identity presented lower perceived discrimination, serving this variable as a protective factor. When comparing the study variables among the two ethnic groups, only perceived discrimination presented a difference. These findings are consistent with previous research.